The Influence of Leadership Spirit and Creativity on Technopreneur-Based Entrepreneurial Interest in Vocational Education - Sudarma, Rio Tirta; Budiastuti, Pramudita (DPTE FT UNY, 2024)
The lack of interest in technopreneur-based entrepreneurship raises concerns about stu-dents' readiness to face the demands of an ever-changing and dynamic job market. There-fore, this research aims to understand the factors that influence interest in technopreneur-based entrepreneurship, especially students in Vocational Education related to leadership and creativity. The research method used was a survey followed by data collection through questionnaires distributed to Vocational Education students, followed by multiple regression analysis using the T test and F test to test the three proposed hypotheses. The research results show that the spirit of leadership and creativity significantly influences the entrepreneurial interest of technopreneur-based Vocational Education students. These two variables together explain most of the variation in entrepreneurial interest, with 91.4% of the variation explained by the combination of the two factors. These findings highlight the importance of developing leadership qualities and stimulating student creativity to foster interest and success in technopreneur-based entrepreneurship.